Oxygen Consumption and BB Rattus novergicus Obesity Sonde Treatment Glucomanan Porang Tubers and Moringa Leaf Extract - Sari, Mustika Arum Mayang; Setyaningsih, Endang (Universitas Muhammadiyah Surakarta, 2023)
Obesity or overweight is a disorder of the amount of weight that results in excessive accumulation of body fat and can pose a risk to the health of the body. This results in metabolism in the body and ends up increasing oxygen consumption in the body. The purpose of the study was to determine the amount of oxygen consumption and body weight of obese white rats (Rattus norvegicus) in the treatment of glucomannan porang tubers (Amorphopallus muelleri Blume) and Moringa leaf extract (Moringa oleifera). The research methods used are (1) Experimental methods prepared with Complete Random Design (RAL) in the form of Posttest Only Design using 8 treatment groups, (2) Documentation methods by documenting tools, research process materials and research results, (3) Literature methods by collecting data by looking for references to books, national and international journals and scientific papers. The results of this study stated the treatment of P2 with a body weight of 290 g with a volume of 9.93 x 10-4 ml / g.min. From this it can be concluded that the amount of oxygen 9.93 x 10-4 body weight 290 g results in increased oxygen consumption.